Lymph Node Response to Neoadjuvant Chemotherapy as an Independent Prognostic Factor in Metastatic Esophageal Cancer. Issue 6 (June 2021) - Urakawa, Shinya; Makino, Tomoki; Yamasaki, Makoto; Tanaka, Koji; Miyazaki, Yasuhiro; Takahashi, Tsuyoshi; Kurokawa, Yukinori; Motoori, Masaki; Kimura, Yutaka; Nakajima, Kiyokazu; Mori, Masaki; Doki, Yuichiro
Abstract : Objective: The aim of this study was to evaluate primary tumor (PT) and lymph node (LN) responses to neoadjuvant chemotherapy (NACT) for predicting long-term survival in patients with metastatic esophageal cancer (EC). Background: In evaluating NACT responses in patients with EC, imaging modalities typically target the PT in the esophagus, which is unmeasurable. Targeting measurable organs, like positive LNs, might provide more accurate assessments. Methods: We enrolled 251 patients with EC and clinically positive LNs that underwent curative resections, after triplet NACT. The percent reduction of PT area was measured with bidimensional computed tomography. The LN response was defined as the percent reduction of the sum of the short diameters in all positive LNs. Results: NACT reduced PTs and LNs by (median, range) 58.0% (38.1–94.9) and 34.5% (46.2–68.2), respectively. Based on the receiver-operating characteristic analyses for predicting a histological response and a 10% stepwise cutoff analyses of recurrence-free survival (RFS), responder/nonresponder cutoff values were ≥60% for PT area reductions and ≥30% for LN size reductions. 39.6% of patients showed discordant PT and LN responses. Compared with PT-responders, LN-responders had significantly less advanced pN ( P < 0.0001) and pM ( P = 0.015) in addition to less advanced pT ( P < 0.0001) and better histological responses ( P < 0.0001), and closer correlations to lymphatic, distant metastases and dissemination. A multivariate analysis of RFS identified 2 independent prognostic factors: the LN response [hazard ratio (HR) = 2.51, 95% confidence interval (CI) = 1.63–3.95, P < 0.0001] and the pN (HR = 2.72, 95% CI = 1.44–5.64, P = 0.0016), but not the PT response. Conclusions: The LN response to NACT predicted long-term survival more precisely than the PT response in patients with metastatic EC. Abstract : Supplemental Digital Content is available in the text